PENDEKATAN DALAM ANALISIS WACANA KRITIS - Masitoh Masitoh (Universitas Muhammadiyah Kotabumi, 2020)
Abstract The basic understanding of critical discourse analysis is that discourse is not only understood as an object of language study. Language in the analysis of critical discourse in addition to the text also in the context of language as a tool that used for specific purposes and practices in the scope of setting, situation, history, power, and ideology. The Context is everything outside of the language itself. The main purpose of critical discourse analysis is to reveal the blur in discourse. To analyze the critical discourse, there were several approaches presented by experts, as follow; First, Norman Fairclough's approach produces a three-dimensional framework in understanding and analyzing discourse, namely the dimensions of discourse as text, discourse as discursive practice, and discourse as social practice by utilizing semiotics. Second, the approach to critical discourse analysis offered by Van Leeuwen centers on describing social actors in discourse and explaining how social actors were represented in a text. Third, Van Dijk's discourse analysis approach assembles sociocognitive ideologies, so that critical discourse analyzers could reveal ideologies hidden behind the text. Fourth, Wodak proposes a historical-discourse approach, which always integrates analysis of the historical context into the interpretation of discourse. While the fifth, Sara Mills’ approach emphasizes how women who were always marginalized were displayed in the text.